Inflation Caused by Remittance in Nepalese Economy - Nepal, Netra Prasad (Adhyayan Journal, 2022)
Present paper aims at identifying the impact of remittance on inflation in Nepalese economy through econometric methodology such as Cointegration test, Vector Error Correction Models (VECM) and Granger Causality tests. Using annual data series from 1990/91 to 2018/19, the variables under study are found to be cointegrated as reported by Johansen’s cointegration test. The VECM also shows the short run and long run relationship between the variables. The Granger Causality test shows the uni-directional causality from remittance to inflation. Present paper focuses on the emphasis of using remittance on capital formation. The returned migrants are to be provided soft loans to establish domestic and small-scale industries. The returned migrants are to be encouraged to forced saving.